ART AND LANDSCAPE: time and space in the work Monument to the continental drift of Thiago Pitta - Alonso, Alex; Silva, Camila Calolinda da; Ghizzi, Eluiza Bortolotto (Revista do Colóquio, 2021)
The article is inserted in the context of the relations of art with space and time, especially from a vision of art that walks through the interstices between the artistic object and the landscape. Seeking to accompany ways of signifying space-time in contemporary art, he proposes to analyze the work Monument to the continental drift, by Thiago Rocha Pitta, in his dialogue with the theme. In addition to the work itself, reflections by different authors on time and space and Krauss on sculpture as an expanded field are taken as a reference. The spatiotemporal relations appear in Pitta’s work in three layers that allow dealing with the poetic, the sensitive, and the cognitive in art.